Analisa Perawatan Diesel Engine Generator (DEG) Tunu South Production Platform Pertamina Hulu Mahakam - Abdul Zain; Wildan Alif Imam Putra (Jurnal Teknik Mesin Sinergi, 2020)
Routinely, oil and gas activity at PT Pertamina Hulu Mahakam has been supplying electric power by Diesel Engine Generator (DEG). Writer takes this research object because Diesel Engine Generator is one of the critical asset with intention of understand preventive maintenance procedural steps, frequent faults occur during electrical generation system. Writer takes this analysis based on operational history from least one year occured fault auxiliary system frequently. Such as current transformer and magnetic pick-up which involving a process shutdown and loss electrical power causes less contribution on Tunu South Production Platform. And other reason cause unplanned shutdown were during maintenance on 6 monthly nor Yearly didn’t checking on auxiliary system, The procedure wasn’t update causes unplanned shutdown possibility in the further.